The Urgency of Humanistic Education in Learning - Kinana Dwinta Sukma; Cindy Oktariani; Muhammad Fadhli Perdana Lubis (Journal of Contemporary Gender and Child Studies, 2024)
To help the younger generation be more agile in navigating the times, education is seen as a form of solution. Education is a forum to form insightful human beings. The substansial progress of society, nation, and state. Therefore, an education that humanizes man is needed. Reflecting on this, humanist values show their urgency as one of the alternatives that can solve the problem. The education provided by humanists is democratic, and emancipatory, and focuses on the growth of human qualities both on a physical and psychic level. Humanist education has the harmony that a person can develop, harmonious from all elements of humanity, and recognize and appreciate everyone's humanity. This research uses qualitative methods with a descriptive-analysis approach and collects information using literature studies. The results showed that humanist values are very important to be internalized to avoid the negative impacts of uneven application of education, such as techno centrism and commercialization of education. Therealization of humanist values can be realized using methods, media, and learning models as needed, as well as contextual learning content.